Walking autonomy. Extension and cooperativism experience in the women and sexual dissident’s prison in the city of Santa Fe (Teresa Vigetti: Revista de Trabajo Social, 2025)
In this work we are interested in reconstructing the work we have been doing since 2021 as an extension team. In this instance we intend to contribute to the reflection on the university extension activities that gave rise to an organizational and collective process that develops inside the prison and then in the post confinement. From this experience, we will make visible the strategies and articulations built from an extension team of the UNL with a community that goes through different problems, and that is characterized by suffering effects as a consequence of prison confinement. Consequently, the focus of our work -as an extension team- was centered on the problematization of the socioeconomic vulnerability of this population.The relationship built between these actors (university students and detainees/inmates) was oriented to become a facilitator in the access to rights and is inscribed in an intervention that takes place “in spite of confinement”. This approach moves away from the notions of rehabilitation and treatment, to focus on inclusion and the need for public policies that expand rights both “during” and “after” incarceration. Along this path, we have jointly generated instances of training in cooperativism, actions to make the cooperative's work visible, meetings to exchange experiences with social organizations, as well as the link with different public policies related to women's access to work and economic autonomy with a gender perspective.
Keywords: extensionist practices; experience; women's cooperatives; prisons; post-penitentiary